Al-Taghayyurāt al-Ṣawtīyyah bayna al-Lughatayn al-ʻArabīyyah wa al-Tāmiliyyah: Dirāsah Taqābuliyyah - Sithy Shathifa, Mohammed Cassim; Ali, Asem Shehadeh (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Sounds affect each other. It brings to change one of the sounds. The phonological changes that occur as a result of the influence of sounds on some of them are; assimilation, dissimilation, and replacement. The question